The Effect of Fertilizer And Chicken Manure On N Uptake and Growth of Maize Crop (Zea Mays L.)On Inceptisol Kwala Bekala. - Rezeki Ayu Citra Utama Nasution; Madjid Damanik; Alida Lubis (Universitas Sumatera Utara, 2018)
The aim of the research was to examine the effect of fertilizer and chicken manure on N uptake and growth of maize crop (Zea mays L.) on Inceptisol Kwala Bekala. This research was contacted at Rumah Kasa, Laboratory of Chemistry and Soil Fertility, PT. Nusa Pusaka Kencana Analytical Laboratory & QC (Asian Agri Group) and Research Center of the Faculty of Agriculture, University of North Sumatra. This research used factorial randomized block design consisting of 2 factors with 3 replications of factor I: urea fertilizer (U) with 4 dosage levels: U0= 0 g / polybag, U1 = 1g / polybag, U2 = 1.5g / Polybag, U2 = 2g / polybag and factor II: chicken manure (A) with 4 dosage levels ie: A0 = 0 g / polybag, A1 = 50 g / polybag, A2 = 100 g / polybag, A3 = 150 g / Polybag.The results show that the application of highly significant fertilizer improves N uptake. The provision of chicken manure was highly significant to the increase of soil N uptake and plant height. The best treatment on urea fertilizer U1 = 1g / polybag and chicken chicken fertilizer A3 = 150 g / polybagKeywords: chicken manure, Inceptisol N uptake, Urea